Estimating Packet Delivery Ratio for Arbitrary Packet Sizes Over Wireless Links - Jacobsson, Martin; Rohner, Christian (IEEE communications letters, 2015)
Real life measurements show that on a given wireless link, the packet delivery ratio of different packet lengths varies with longer packets experiencing lower delivery ratios. In this letter, we measure this effect in detail over several different wireless links and technologies. Our results show that the current models are not entirely correct. Hence, we propose a simple modification that rectifies this behavior. Using this new model, we look at how link quality estimation methods can be enhanced to include this modification. Our study shows that the use of two different packet lengths or simple compensation can be used to achieve significantly better estimation of link quality.